Hermann Vinterberg og C. A. Bodelsen: Dansk-engelsk Ordbog 3. udgave. Redaktion: Viggo Hjørnager Pedersen. Gyldendal, 1990 - Lauridsen, Karen M. (HERMES - Journal of Language and Communication in Business, 1991)
Vinterberg and Bodelsen's Danish-English dictionary has now been published in its third, revised edition. As a natural consequence of the development in society as a whole, Danish and English usage has changed considerably since the second edition was published in the mid-1960s, thousands of new words have been added to both languages, and a range of words and expressions have undergone a change in meaning. The present review focusses on seeing whether these changes are reflected in the selection of entries and the translation equivalents offerede in the dictionary and concludes that, even though there are about 100,000 changes (of which approximately 50,000 are additions) in the new edition, a wide range of entries are not sufficiently updated. Given the development in computer software and lexicography within the last two decades, it must be concluded that the dictionary is not on the forefront of the development.